Global Business Networks and Cooperation within Supply Chain as a Strategy of High-Tech Companies’ Growth - Milena Ratajczak-Mrozek (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Abstract The specificity of the operation profile of high-tech companies, including the necessity of operating at the international scale may account for the fact that these companies may find in network relationships, business networks and cooperation an essential determinant for growth and competitiveness. Foreign entities should be especially interesting business partners for high- tech companies, as they are often seen as representing more advanced knowledge, resources and experience. The aim of the article is to point out to global business networks (i.e. including both local and foreign entities), and especially to cooperation within supply chain, as an important basis for a growth strategy of a high-tech company. The article adopts assumptions of the network approach as a concept of companies cooperation. An analysis of the author’s own as well as secondary empirical research, with the focus on high- tech companies located in Poland is presented. In particular, the data from own research of 62 high-tech companies in Poland conducted in the first half of 2011 is analysed. It shows that the high-tech companies placing great importance on cooperation within supply chain demonstrate a higher growth and level of competitiveness than the companies which do not ascribe such importance (bearing in mind that supply chain forms an important part of a business network).